2020
DOI: 10.14202/vetworld.2020.1174-1181
|View full text |Cite
|
Sign up to set email alerts
|

Dermatophytosis in companion animals: A review

Abstract: Dermatophytosis, a zoonotic disease, is caused by fungi of three main genera, namely, Micropsorum, Trichophyton, and Epidermophyton. Specific lesions of dermatophyte infections are localized in the face, legs, and/or tail. Skin lesions in infected animals demonstrate localized alopecia, erythema, and crust, which are more commonly known as ringworm. Factors that affect dermatophytosis include the dermatophyte species; virulence factors of the agent; and the immune status, age, and sex of the host. High… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 80 publications
2
25
0
5
Order By: Relevance
“…The results of fungal culture in this study indicate that dermatophytosis cases in cats in Yogyakarta are dominated by M. canis species. The results of this study are similar to the findings of previous researchers who explained that three most common dermatophyte species infecting cats and dogs are M. canis, M. gypseum, and T. mentagrophytes (Indarjulianto et al, 2014;Dong et al, 2016;Grable, 2019;Moriello et al, 2019;Paryuni et al, 2020). Research results by Moriello and Deboer (2012) and Koussidou-Eremondi et al (2005) also showed that M. canis is a dermatophyte species that is commonly found in cats and is known to be the main dermatophyte found in humans.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The results of fungal culture in this study indicate that dermatophytosis cases in cats in Yogyakarta are dominated by M. canis species. The results of this study are similar to the findings of previous researchers who explained that three most common dermatophyte species infecting cats and dogs are M. canis, M. gypseum, and T. mentagrophytes (Indarjulianto et al, 2014;Dong et al, 2016;Grable, 2019;Moriello et al, 2019;Paryuni et al, 2020). Research results by Moriello and Deboer (2012) and Koussidou-Eremondi et al (2005) also showed that M. canis is a dermatophyte species that is commonly found in cats and is known to be the main dermatophyte found in humans.…”
Section: Resultssupporting
confidence: 92%
“…Moriello et al (2017) and Bianchi et al (2017) also stated that dermatophyte infection will manifest as superficial clinical signs, starting with the presence of erythema then followed by the appearance of scales and crusts, then alopecia. Paryuni et al (2020) mentioned that dermatophytes are known to be unable to grow in the center of the lesion (an area that is experiencing inflammation), so the infection will spread centrifugally to the periphery of the lesion resulting in round lesions such as rings or ringworms.…”
Section: Resultsmentioning
confidence: 99%
“…13 Dermatophytes consist of 40 species of fungi derived from three genera, namely, Micropsorum, Trichophyton, and Epidermophyton. 14 The two genera of fungi that are the main causes of dermatophytosis in animals (especially in dogs and cats) are Microsporum spp. and Trichophyton spp.…”
Section: Introductionmentioning
confidence: 99%
“…However, in order to have an accurate diagnosis, it is necessary to carry out the isolation of the fungus through cultures and microscopic identification. For the mycological culture, it is necessary to obtain a sample of the infected tissue by scraping or plucking the affected area, but first it is important to clean it in order to reduce the presence of environmental contaminating fungi (Parmar et al 2018;Paryuni et al 2020). The main disadvantage of conventional diagnosis is the growth time of dermatophytes.…”
Section: Introductionmentioning
confidence: 99%